Linkages between rumen microbiome, host, and environment in yaks, and their implications for understanding animal production and management - Wang, Weiwei; Dong, Yuntao; Guo, Wei; Zhang, Xiao; Degen, A. Allan; Bi, Sisi; Ding, Luming; Chen, Xiang; Long, Ruijun (Frontiers in Microbiology, 2024)
Qinghai-Tibetan Plateau livestock is of great importance for the livelihood of the local inhabitants and the plateau ecosystem. The natural, harsh environment shaped local livestock uniquely for adaptation while providing the eco-services for the animals.Over a long time, morphologically and physiologically, the yaks have evolved unique genes and metabolic mechanisms (nitrogen and energy) to adapt to the Qinghai-Tibetan Plateau. The rumen microbiota has also co-evolved with the host and contributed to the host's adaptation to the environment. Understanding the complex linkages among the rumen microbiota, the host, and the environment is essential to optimizing rumen function to meet growing demands for animal products while minimizing the environmental impact of ruminant production. However, we still know little about the mechanistic bases of host-rumen microbiome-environment linkages and how they ultimately benefit the animal in adapting changes to serve their performance. Here we piece together a view of the yak adaptation to the Qinghai-Tibetan Plateau ecosystem by summarizing the natural selection and nutritional features of yaks, integrating the key aspects of its rumen microbiome with the host metabolic efficiency and homeostasis. This homeostasis results in higher feed digestibilities, higher rumen microbial protein production, higher short-chain fatty acids (SCFAs) concentrations, and lower methane emission services for yaks when compared with other low-altitude ruminants. The rumen microbiome forms a multi-synergistic relationship among the services, their communities, genes, and enzymes. The rumen microbial proteins and SCFAs act as precursors that directly impact the milk composition or adipose accumulation, improving the milk or meat quality, resulting in a higher protein and fat content in yak milk, a higher percentage of protein and abundant fatty acids in yak meat when compared to the dairy cow or cattle. The hierarchical interactions among the climate, forage, rumen microorganisms, and host genes reshaped the animal's survival and performance. An integrating and interactive understanding of the host-rumen microbiome environment was established, the understanding of these concepts is valuable for agriculture and our environment and also contributes to a better understanding of microbial ecology and evolution in anaerobic ecosystems and the host-environment linkages to improve animal production.